Pengaruh Partisipasi Penganggaran pada Senjangan Anggaran dengan Ketidakpastian Karir sebagai Variabel Pemoderasi - Srimaheni, Ni Wayan Oka; Widanaputra, A.A. G.P. (E-Jurnal Akuntansi, 2018)
This study aim to examine and to get empirical evidence, the influence of paticipative budgeting on budgetary slack with career uncertainty as the moderating variable. This research was conducted at the OPD of Klungkung regency in the form of “ dinas ” and “ badan ”, with 61 respondents including heads of “ dinas/badan” , heads of finance and heads of planning in each OPD. The analysis technique used Moderation Regression Analysis (MRA). The result indicate that the variable of career uncertainty is not able to moderate the influence of budgetary participation on budget slack. This may happen because when an employee creates a budget slack, she/he does not think about whether or not to participate in the realization of the budget. Keywords : career uncertainty, paticipative budgeting, budgetary slack.